O Serviço social nas organizações não-governamentais: tendências e particularidades - Duarte, Janaína Lopes do Nascimento (2007)
The present study is about the professional exercise of the Social Worker in ONGs associated with the ABONG in Natal city, state of Rio Grande do Norte, referring to the work conditions, claims and professional responses in front of the capital restructuration circumstances. The group of socio-historical transformations, as a result of the after-1970 dynamic capitalism, conducts a process of new configurations in the relationship between State and society that directly affect the social question nowadays, destroying social rights historically conquered for the workers. In this context, the ONGs assume a strategical social function of the social question, contributing with the change of responsibilities with the social from the State to the third sector. This social movement causes changes to the Social Work since this is one of the professions that act on the immediate expressions of the social question. After a qualitative research based on a theoricalmethodological critical and dialectical perspective, it was possible to discover some contradictions, details and tendencies of the professional exercise of the Social Worker in ONGs. Summarizing, the results of the research show that: a) it was detected a tendency of precarization, instability, insecurity, no-articulation, no-profissionalization of the professionals in the work conditions; b) demands are associated with a moment of the capital re-ordering, where new professional exigencies and responsibilities are related with capital necessities in the period of structural crisis; c) limits and contradictions are present in a professional daily work mainly in function of the characteristics of gestation and functioning of the ONGs; d) the professionals that were interviewed show significant difficulties in a articulation between the professional daily work in organizations and the totality of the social processes, limiting the capability of doing critics to the requisitions imposed by the capital